2007
DOI: 10.1080/07373930601160957
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Drying of Grass Seeds (Brachiaria brizantha) in Fluidized Beds

Abstract: A modified three-phase model is developed to simulate the drying of Brachiaria brizantha in fluidized beds. In this new model, the constitutive equation of drying kinetics is formulated including both the constant rate and the falling rate mechanisms; the seed shrinkage is taken into account during all drying operation and the transition between bubbling to slugging regime is delineated for estimating the bubble velocity and size. Such modifications improve the mathematical model to better simulate the drying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Three copper-constantan thermocouples are installed inside the column to measure: the inlet air temperature, T g0 , (thermocouple inserted just before the distributor plate); the solid-gas emulsion temperature, T bed , or the solid temperature, T s , (thermocouple placed 0.10 m above the air distributor) and the outlet air temperature, T gL , (thermocouple placed at z = 0.38 m from the base of the column). The solid temperature, T s , is measured during a short time interval in which the bed is collapsed; details of this method are discussed by Rizzi Jr. et al (2005). A thermocouple adhered to the outer column wall (at z =0.38 m) records the column wall temperature, T w .…”
Section: Methodsmentioning
confidence: 99%
“…Three copper-constantan thermocouples are installed inside the column to measure: the inlet air temperature, T g0 , (thermocouple inserted just before the distributor plate); the solid-gas emulsion temperature, T bed , or the solid temperature, T s , (thermocouple placed 0.10 m above the air distributor) and the outlet air temperature, T gL , (thermocouple placed at z = 0.38 m from the base of the column). The solid temperature, T s , is measured during a short time interval in which the bed is collapsed; details of this method are discussed by Rizzi Jr. et al (2005). A thermocouple adhered to the outer column wall (at z =0.38 m) records the column wall temperature, T w .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the measured data, it was observed that the mass and heat transfer correlations of Equations , , and were not adequate to predict the required time for biomass drying. Therefore, a new correlation for the mass transfer coefficient ( k m ) that considers the solid humidity ratio and preserves the dependence on the solid‐phase temperature was derived, which is a reasonable proposition according to Rizzi . The resulting final expression is as follows: km=x1exp[]x2Tsx3ωs, where x 1 , x 2 , and x 3 are adjustment constants and T s is given in °C and ω s in kg kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Physically, Equation is not adequate for wet microalgae biomass because it was derived for grass seeds, which present a much lower water content than the wet microalgae biomass. Therefore, the adjusted values for x 1 and x 2 based on wet microalgae biomass experiments are quite different from the ones obtained in Equation for grass seeds, and additionally, it was necessary to include a dependency on biomass humidity ratio, as shown in Equation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations